Separação dos poderes, ativismo judicial e tensão institucional: análise da relação entre judiciário e legislativo na teoria constitucional e reflexão sobre o caso brasileiro - Amorim, Samira Macêdo Pinheiro de (2015)
This paper aims at analyzing the relationship between the Legislative and the Judiciary powers by investigating the theories of the last word – which defends the supremacy of one over the other – and by evaluating theories of institutional dialogue. It also investigates this relationship in the Brazilian context. Initially, we present work premises based on research on the theory of separation of the three powers amongst its historical development and its current concept, on the constitutionalism and constitutional control, as well as on the expansion of constitutional jurisdiction and judicial activism, aiming at understanding the current issues involving institutional conflict. After this, we present the foundation of the theories of the last word, the constitutional interpretation and the arguments used in order to defend the judicial and legislative supremacy. Futher on, beyond the theory of the last word, we investigated the dialogic theories, their contribution and the experiences in the dialogic constitutional jurisdiction of Canada, Israel, New Zealand and United Kingdom. Lastly, we analyze the institutional relationship between Brazilian Legislative and Judiciary powers, questioning the judicial supremacy and evaluating constitutional mechanisms favoring institutional dialogues, such as the absence of correlation of the decisions of the Supreme Federal Court and Legislative power, the aspects that involve the legislative omissions, among others. We also explore the Constitutional Amendment Proposals 3 (2011), 33 (2011) and 171 (2012), which represent responses from the legislative power to judicial activism and which aim at creating an institutional dialog among the powers. This paper demonstrates that dialogic theories have several different facets and can create many advantages to the democratic system. However, the alien experiences cannot be imported without adequate study of particular aspects of the Brazilian constitutional jurisdiction. We state that Brazil already has mechanisms that allow dialog among Legislative and Judiciary powers, which should be explored adequately by these powers and by doctrine. For these conclusions, we use explanatory and exploratory methods, performing bibliographical and documentation research.